Providing Culturally Competent Services for American Indian and Alaska Native Veterans to Reduce Health Care Disparities - Noe, Timothy D. (American Public Health Association, 2014)
Objectives. We conducted an exploratory study to determine what organizational characteristics predict the provision of culturally competent services for American Indian and Alaska Native (AI/AN) veterans in Department of Veterans Affairs (VA) health facilities. Methods. In 2011 to 2012, we adapted the Organizational Readiness to Change Assessment (ORCA) for a survey of 27 VA facilities in the Western Region to assess organizational readiness and capacity to adopt and implement native-specific services and to profile the availability of AI/AN veteran programs and interest in and resources for such programs. Results. Several ORCA subscales (Program Needs, Leader’s Practices, and Communication) statistically significantly predicted whether VA staff perceived that their facilities were meeting the needs of AI/AN veterans. However, none predicted greater implementation of native-specific services. Conclusions. Our findings may aid in developing strategies for adopting and implementing promising native-specific programs and services for AI/AN veterans, and may be generalizable for other veteran groups.